Antibacterial activity of the Pangium edule Reinw seed against Staphylococcus aureus, Escherichia coli and Salmonella enterica / Silva Lynn Yasun - Yasun, Silva Lynn (2017)
Pangium edule is an indigenous plant where it has been reported to have the antibacterial activity. Thefore the extract of the endocarp and kernel of the Pangium edule seed were extracted to determine the antibacterial activity against the Staphylococcus aureus, Escherichia coli and Salmonella enterica. The methods used in this study were the disc diffusion assay, Minimum Inhibitory Concentration (MIC) followed by Minimum Bacteria Concentration (MBC). Based on the results obtained on this study, the ethanolic kernel extract of the Pangium edule was intermediate susceptible against the Staphylococcus aureus with the zone of inhibition of 16.67 ± 2.08 mm. From the MIC analysis, the lower concentration of the kernel extract that can inhibit the Staphylococcus aureus was 0.65 mg/ml. Whereas, the result for the MBC analysis, the bacteria showed the bacteriostatic property, as there were bacteria growth from the minimum concentration of MIC value. In conclusion, the ethanolic extract of Pangium edule kernel have the antibacterial activity against the Staphylococcus aureus. Thus as for recommendation it can be another alternative source of antibiotics for treat the disease cause by the Staphylococcus aureu.